Diagnostic properties of differing BP thresholds for adverse pregnancy outcomes in standard-risk nulliparous women: A secondary analysis of SCOPE cohort data - Slade, Laura; Blackman, Maya; Mistry, Hiten D.; Bone, Jeffrey N.; Wilson, Milly; Syeda, Nuhaat; Poston, Lucilla; von Dadelszen, Peter; Magee, Laura A. (PLoS medicine, 2025)
In 2017, the American College of Cardiology and American Heart Association (ACC/AHA) lowered blood pressure (BP) thresholds to define hypertension in adults outside pregnancy. If used in pregnancy, these lower thresholds may identify women at increased risk of adverse outcomes, which would be particularly useful to risk-stratify nulliparous women. In this secondary analysis of the SCOPE cohort, we asked whether, among standard-risk nulliparous women, the ACC/AHA BP categories could identify women at increased risk for adverse outcomes. Included were pregnancies in the international SCOPE cohort with birth at ≥20 weeks' gestation, 2004 to 2008. Women were mostly of white ethnicity, in their 20s, and of normal-to-overweight body mass index (BMI). Excluded were pregnancies ending in fetal loss at <20 weeks' gestation, and those terminated at any point in pregnancy. Women were categorized by highest BP during pregnancy, using ACC/AHA criteria: normal (BP <120/80 mmHg), "Elevated BP" (BP 120 to 129 mmHg/<80 mmHg), "Stage-1 hypertension" (systolic BP [sBP] 130 to 139 mmHg or diastolic BP [dBP] 80 to 89 mmHg), and "Stage-2 hypertension" that was non-severe (sBP 140 to 159 mmHg or dBP 90 to 109 mmHg) or severe (sBP ≥160 mmHg or dBP ≥110 mmHg). Primary outcomes were preterm birth (PTB), low birthweight, postpartum hemorrhage, and neonatal care admission. Adjusted relative risks (aRRs) and diagnostic test properties were calculated for each outcome, according to: each BP category (versus "normal"), and using the lower limit of each BP category as a cut-off. RRs were adjusted for maternal age, BMI, smoking, ethnicity, and alcohol use. Of 5,628 women in SCOPE, 5,597 were included in this analysis. When compared with normotension, severe "Stage 2 hypertension" was associated with PTB (24.0% versus 5.3%; aRR 4.88, 95% confidence interval, CI [3.46 to 6.88]), birthweight <10th centile (24.4% versus 8.8%; aRR 2.70 [2.00 to 3.65]), and neonatal unit admission (32.9% versus 8.9%; aRR 3.40 [2.59 to 4.46]). When compared with normotension, non-severe "Stage 2 hypertension" was associated with birthweight <10th centile (16.1% versus 8.8%; aRR 1.82 [1.45 to 2.29]) and neonatal unit admission (15.4% versus 8.9%; aRR 1.65 [1.31 to 2.07]), but no association with adverse outcomes was seen with BP categories below "Stage 2 hypertension." When each BP category was assessed as a threshold for diagnosis of abnormal BP (compared with BP values below), only severe "Stage 2 hypertension" had a useful (good) likelihood ratio (LR) of 5.09 (95% CI [3.84 to 6.75]) for PTB. No BP threshold could rule-out adverse outcomes (i.e., had a negative LR <0.2). Limitations of our analysis include lack of ethnic diversity and use of values from clinical notes for BP within 2 weeks before birth. This study was limited by: its retrospective nature, not all women having BP recorded at all visits, and the lack of detail about some outcomes. In this study, we observed that 2017 ACC/AHA BP categories demonstrated a similar pattern of association and diagnostic test properties in nulliparous women, as seen in the general obstetric population. BP thresholds below the currently used "Stage 2 hypertension" were not associated with PTB, low birthweight, postpartum hemorrhage, or neonatal unit admission. This study does not support implementation of lower BP values as abnormal in nulliparous pregnant women.